ANALYSIS IMPORT POLICY OF SOYBEAN ON ECONOMICS PERFORMANCE OF INDONESIAN SOYBEAN - Azizah, Muthiah Abda; Syafrial, Syafrial; Suhartini, Suhartini (HABITAT, 2015)
Trade liberalization is closely related to the opening of market access for Indonesian products to the world and vice versa. Since the soybean trade out of BULOG control began in 1998, soybean imports increased very rapidly (Sudaryanto and Swastika, 2007). This research aims to determine the general picture of soybean economy, factors analyses that influence the economic performance of Indonesian soybean and findings the alternative of policies that can reduce soybean imports in Indonesia. Methods of data analysis are descriptive analysis, 2SLS simultaneous equations, and simulation of policy alternatives. Results of the analysis of the factors that affect the economic performance of Indonesian soybean, consists of 1) The area of soybean harvest is influenced significantly by the price of domestic soybean and domestic prices of corn, 2) Productivity soybean influenced significantly by the domestic prices of soybean and fertilizer prices, 3) soybean demand influenced significantly by population, domestic prices of soybean, 4) domestic prices of soybean significantly affected by world prices of soybean, exchange rates, and soybean supply, 5) Imports of soybean influenced significantly by the domestic demand of soybean and soybean production. Therefore, policy scenarios should be made to reduce soybean imports, including by carrying out the expansion of soybean harvest policy, the policy of increasing the productivity of soybean, the policy of subsidizing the price of fertilizer.